Microplastic Identification via Holographic Imaging and Machine Learning. (13th January 2020) - Bianco, Vittorio; Memmolo, Pasquale; Carcagnì, Pierluigi; Merola, Francesco; Paturzo, Melania; Distante, Cosimo; Ferraro, Pietro
Abstract : Microplastics (MPs) are a major environmental concern due to their possible impact on water pollution, wildlife, and the food chain. Reliable, rapid, and high‐throughput screening of MPs from other components of a water sample after sieving and/or digestion is still a highly desirable goal to avoid cumbersome visual analysis by expert users under the optical microscope. Here, a new approach is presented that combines 3D coherent imaging with machine learning (ML) to achieve accurate and automatic detection of MPs in filtered water samples in a wide range at microscale. The water pretreatment process eliminates sediments and aggregates that fall out of the analyzed range. However, it is still necessary to clearly distinguish MPs from marine microalgae. Here, it is shown that, by defining a novel set of distinctive "holographic features, " it is possible to accurately identify MPs within the defined analysis range. The process is specifically tailored for characterizing the MPs' "holographic signatures, " thus boosting the classification performance and reaching accuracy higher than 99% in classifying thousands of items. The ML approach in conjunction with holographic coherent imaging is able to identify MPs independently from their morphology, size, and different types of plastic materials. Abstract : Microplastic (MP) pollutants are automatically identified with high accuracy in prefiltered water. Herein, holographic phase‐contrast imaging is combined with machine learning to distinguish between a wide class of plastic items and marine microalgae over a wide range of scales. This work paves the way for automatic high‐throughput inspection of natural water to map the abundance and distribution of MPs.